(macro-) Evolutionary ecology of parasite diversity: From determinants of parasite species richness to host diversification. Issue 1 (April 2015) - Morand, Serge
Graphical Abstract Asymmetry in host and multi-parasite interactions as a framework for investing the likely determinants of parasite species richness and its ecological and evolutionary impacts on host